CHRONIC DIGITAL STRESS AND DOPAMINE DYSREGULATION: A SYSTEMATIC REVIEW OF THE NEUROBIOLOGICAL EFFECTS OF SOCIAL MEDIA USE - Monika Banaszek,; Katarzyna Kleszczewska,; Agnieszka Pruska,; Natalia Senatorska,; Julia Rarok,; Daria Godlewska,; Hanna Pietruszewska,; Agata Panfil,; Julia Błocka,; Agata Lurka, (International Journal of Innovative Technologies in Social Science, 2025)
Background: The dynamic growth of social media has led to unprecedented levels of digital engagement, contributing to a phenomenon known as chronic digital stress. A growing body of research indicates that this type of stress may affect the brain's reward system, particularly the pathways regulated by dopamine. Understanding these mechanisms is crucial for identifying the neurobiological effects of excessive social media use.Objective: The aim of this systematic review is to synthesise current evidence on the relationship between chronic digital stress and dopamine dysregulation, with a particular focus on neuroimaging, neurochemical, and behavioural findings.Methods: The PubMed, Scopus, Web of Science, and PsycINFO databases were searched for publications from 2020 to 2025 using keywords such as “digital stress”, “dopamine”, “social media”, and “reward system”. Studies assessing dopaminergic activity, stress markers, or behavioural changes associated with social media exposure were included in the analysis.Results: Analysis of the available literature revealed a consistent relationship between excessive social media use and changes in dopaminergic signalling, including reduced receptor sensitivity, reward anticipation disorders, and stress-related modulation of dopamine release. Similarities in neural mechanisms to those seen in behavioural addictions were also observed.Conclusions: Chronic digital stress appears to affect the dopaminergic system in a manner similar to other forms of addictive behaviour, contributing to emotional dysregulation and reduced cognitive control. Future research should focus on longitudinal and neurobiological analyses to establish causal relationships and develop potential interventions.